1990
DOI: 10.1002/1097-0142(19900101)65:1<157::aid-cncr2820650130>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Medullomyoblastoma in an adult

Abstract: Medullomyoblastoma is a rare histologic variant of medulloblastoma. Of the 20 cases reported in the literature, 19 were in children ages 2.5 to 10.5 years and one was in a 26-year-old woman. In the reported adult case the myogenic component of the tumor was leiomyosarcomatous. The authors report a case of medullomyoblastoma with a rhabdomyosarcomatous component in a 40-year-old man with light microscopic, immunohistochemical, and ultrastructural findings. The histogenetic theories regarding this tumor include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…MMD presents exceptionally rarely in adulthood and it is reasonable to consider whether this has a prognostic effect. Two case reports in adults with MMD demonstrated survival of less than 1 month [5] and less than 3 years [3]. The findings of these authors provide no evidence to suggest there is any prognostic advantage to presentation in adulthood.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…MMD presents exceptionally rarely in adulthood and it is reasonable to consider whether this has a prognostic effect. Two case reports in adults with MMD demonstrated survival of less than 1 month [5] and less than 3 years [3]. The findings of these authors provide no evidence to suggest there is any prognostic advantage to presentation in adulthood.…”
Section: Discussionmentioning
confidence: 94%
“…The majority of patients have survived less than 1 year from diagnosis [5]. The longest reported survival in a patient treated with either radiotherapy or chemotherapy alone is 4 years [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few cases have survived 3 years post-treatment. 6 Rao et al 18 reviewed the literature to 1990 and reported that 10 of 21 cases of MMB had a very short survival: only 5 cases survived longer than 6 months and 3 patients survived for more than 2 years, emphasizing the poor outcome for MMB patients. Lewis et al 12 reported a case who survived for more than 4 years.…”
Section: Discussionmentioning
confidence: 99%